Trial of liquidation cementation of boreholes at Carpathians oil and gas deposits - Kovalchuk, M.; Tershak, B.; Cheliadyn, L.; Sobol, Kh.; Terlyha, V. (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
Complex geological structure as well as long-term intensive operation of oil and gas deposits in Borislav-Pokutska zone of Carpathians leads to changes in thermo-dynamical parameters of pools, rock deformation and, as a result, to crippling of the boreholes and creasing and damaging of boring casing. The abovementioned actions not only complicate extraction of oil and gas but increase the technological charge on the environment. In this study 3 types of materials were investigated: PCT-I-100 – traditional tamping cement, CREA and CREA-LF tamping mixes produced by dry mixing technology that were designed by authors. Dry mixes are characterized by higher level of SiO2 because of addition of milled sand and provide better cementation quality. Developed materials are characterized by lower dehydration and water reduction, thanks to clearly chosen composition and modern chemical admixtures usage. The method of borehole eliminative cementation is also presented by authors.